2022
DOI: 10.3390/jcm11195724
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Subsets in Patients with Moderate to Severe Acute Respiratory Distress Syndrome for Early Prediction of Death

Abstract: Introduction: In patients with acute respiratory distress syndrome (ARDS), the PaO2/FiO2 ratio at the time of ARDS diagnosis is weakly associated with mortality. We hypothesized that setting a PaO2/FiO2 threshold in 150 mmHg at 24 h from moderate/severe ARDS diagnosis would improve predictions of death in the intensive care unit (ICU). Methods: We conducted an ancillary study in 1303 patients with moderate to severe ARDS managed with lung-protective ventilation enrolled consecutively in four prospective multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…It seems unrealistic that ventilated moderate/severe ARDS patients can be weaned quickly. We think that the following targets are reasonable within the first three days and beyond ARDS management to decrease MV duration as follows: improving oxygenation for PaO 2 /FiO 2 > 150 mmHg [ 48 ], the use of high PEEP [ 49 ] while keeping Pplat < 29 cmH 2 O [ 50 ], and aiming to reduce extrapulmonary organ dysfunction [ 51 ]. Of note, the best strategies to reduce MV duration in patients with ARDS have not been identified yet and require further research.…”
Section: Discussionmentioning
confidence: 99%
“…It seems unrealistic that ventilated moderate/severe ARDS patients can be weaned quickly. We think that the following targets are reasonable within the first three days and beyond ARDS management to decrease MV duration as follows: improving oxygenation for PaO 2 /FiO 2 > 150 mmHg [ 48 ], the use of high PEEP [ 49 ] while keeping Pplat < 29 cmH 2 O [ 50 ], and aiming to reduce extrapulmonary organ dysfunction [ 51 ]. Of note, the best strategies to reduce MV duration in patients with ARDS have not been identified yet and require further research.…”
Section: Discussionmentioning
confidence: 99%
“…PaO 2 /FiO 2 at baseline is not an acceptable predictor for mortality ( 28 ). Although we found that lower PaO 2 /FiO 2 at baseline and at 48 h were associated to ARDS development, only PaO 2 /FiO 2 at 48 h was associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This case serves to highlight several major issues with the current ARDS definition and its management. Firstly, the PaO 2 /FiO 2 ratio is largely a function of ventilator settings [ 2 ]. Secondly, it is plausible that the PaO 2 /FiO 2 ratio on MV would have been below 150 mmHg had the clinicians opted for a PEEP < 12 cmH 2 O.…”
Section: Problems With Ards Definitionsmentioning
confidence: 99%
“…Patients with these features may meet the Berlin definition, but their overall outcome is usually better compared to true ARDS. Enrollment of patients with rapidly improving ARDS or pseudo-ARDS may contribute to the failure of therapeutic clinical trials [ 19 ], paving the way to studies where physiological enrichment is used to overcome this issue [ 2 ]. Severe hypoxemia caused by lobar consolidation is frequently treated as ARDS, when it is possible that specific treatment options would benefit these patients, while they could be spared from the development of ventilator-induced lung injury (VILI) in the unaffected lung [ 20 ].…”
Section: The Pseudo-ards Scenariomentioning
confidence: 99%
See 1 more Smart Citation